Theory-of-mind in individuals with Alström syndrome is related to executive functions, and verbal ability - Frölander, Hans-Erik I.; Möller, Claes; Rudner, Mary; Mishra, Sushmit; Marshall, Jan D.; Piacentini, Heather M.; Lyxell, Björn (Frontiers in Psychology, 2015)
Objective: This study focuses on cognitive prerequisites for the development of Theory-of-mind (ToM), the ability to impute mental states to self and others in young adults with Alström syndrome (AS). AS is a recessively inherited ciliopathic disorder causing progressive hearing loss and juvenile blindness, both of which affect communication, as well as other dysfunctions. Two cognitive abilities were considered; Phonological working memory and Executive functions (EF), both of importance in speech development . Methods: Ten individuals (18–37 years) with AS, and 20 nondisabled individuals matched for age, gender and educational level participated. Sensory functions were measured. Information about motor functions and communicative skills was obtained from questionnaire data. ToM was assessed using Happés strange stories, verbal ability by a vocabulary test, phonological WM by an auditory presented serial-recall task and EF by tests of updating and inhibition. Results: The AS group performed significantly poorer than the control group in both the ToM task and the EF tasks. A relation was established between recall of non-words and EF in the AS group. Updating, but not inhibition, correlated with verbal ability, whereas both updating and inhibition related to the ability to initiate and sustain communication. Individuals with AS displayed a high degree of variance in performance across tasks and those with a relatively high ToM performance performed within the range of the control group, in EF tasks. Poorer ToM and EF performance were related to language perseverance and motor mannerisms. Conclusions: The AS group demonstrated delayed ToM, reduced phonological WM, EF and verbal ability and for the first time an association between ToM and EF in AS was found. This association is suggested to reflect the importance of EF in developing the capacity to perceive and process input from the social environment. Limitations in EF may be related to cerebellar dysfunction.